Recognition of CpG island chromatin by KDM2A requires direct and specific interaction with linker DNA. - Zhou, J; Blackledge, N; Farcas, A; Klose, R (2012)
Up to 70% of human genes are associated with regions of nonmethylated DNA called CpG islands (S. Saxonov, P. Berg, and D. L. Brutlag, Proc. Natl. Acad. Sci. U. S. A. 103:1412-1417, 2006). Usually associated with the 5' end of genes, CpG islands are thought to impact gene expression. We previously demonstrated that the histone demethylase KDM2A is specifically recruited to CpG islands to define a unique chromatin architecture and highlight gene regulatory regions in large and complex mammalian genomes. This targeting relies on a zinc finger CXXC DNA binding domain (ZF-CXXC), but how this demethylase interfaces with CpG island chromatin in vivo remains unknown. Here we demonstrate, using defined chromatin templates in vitro and chromatin profiling in vivo, that nucleosomes are a major barrier to KDM2A binding and that CpG islands are directly interpreted by the ZF-CXXC domain through specific interaction with linker DNA. Furthermore, KDM2A appears to be constrained to CpG islands not only by their nonmethylated state but also by a combination of methylated DNA and nucleosome occlusion elsewhere in the genome. Our observations suggest that both DNA sequence and chromatin structure are defining factors in interpreting CpG island chromatin and translation of the CpG signal. More generally, these features of CpG island recognition suggest that chromatin structure and accessibility play a major role in defining how transcription factors recognize DNA and regulatory elements genome-wide.